Persistence of Cytosine Methylation of DNA following Fertilisation in the Mouse - Li, Yan (Public Library of Science, 2012)
Normal development of the mammalian embryo requires epigenetic reprogramming of the genome. The level of cytosine methylation of CpG-rich (5meC) regions of the genome is a major epigenetic regulator and active global demethylation of 5meC throughout the genome is reported to occur within the first cell-cycle following fertilization. An enzyme or mechanism capable of catalysing such rapid global demethylation has not been identified. The mouse is a widely used model for studying developmental epigenetics. We have reassessed the evidence for this phenomenon of genome-wide demethylation following fertilisation in the mouse. We found when using conventional methods of immunolocalization that 5meC showed a progressive acid-resistant antigenic masking during zygotic maturation which gave the appearance of demethylation. Changing the unmasking strategy by also performing tryptic digestion revealed a persistence of a methylated state. Analysis of methyl binding domain 1 protein (MBD1) binding confirmed that the genome remained methylated following fertilisation. The maintenance of this methylated state over the first several cell-cycles required the actions of DNA methyltransferase activity. The study shows that any 5meC remodelling that occurs during early development is not explained by a global active loss of 5meC staining during the cleavage stage of development and global loss of methylation following fertilization is not a major component of epigenetic reprogramming in the mouse zygote.